The business intelligence use in healthcare and its enhancement by predictive analytics - Mohamed Mahmoud, Mohamed Mahmoud; Mohamadali, Noor Azizah (Seventh Sense Research Group, 2019)
In the last few years the business intelligence systems (BI) had seen a wide spread among organisations in different sectors such as healthcare and it was studied by many researchers. This study aims to describe what are the business intelligence systems, their benefits and challenges especially when its used in healthcare sector. Moreover, this research suggests that the integration of predictive analytics with BI models could give a better understanding especially regarding the effect of information quality and decision-making quality on the organizational growth and performance.The outcomes of this research show that the main benefits of using BI in healthcare is to improve the decision-making b making it better and faster, enhancing hospitals performance, reducing costs, enhance the quality of healthcare provided to patients, and save time. Moreover, the main challenges in healthcare is the problem of data quality, andthe integration of BI with other hospital systems. Therefore, the analysis of previous BI models shows that there is a consensus that BI system maturity and management quality influence the data and information quality which in turn affect positively the users’ satisfaction, BI usage, and the decision-making quality and lead to improve it. While there is some a contradictory opinion which claim that data quality is no more a challenge and does not affect the success of BI systems. Moreover, BI systems have direct and indirect effect on the decision-making quality but there still no research proving its influence on the organizational growth